Validation of a questionary for measuring corbicular pollen consumer preferences via structural equations models (2023)
Boyacá is one of the main bee pollen (or corbicular pollen) producers in Colombia. However, pollen consumer preferences in this region are unknown; therefore, there is no background to develop marketing strategies aiming at profiting beekeepers and consumers. This study presents the design and statistical validation of a questionary to assess the preferences of bee pollen consumers and the model that supports the relationships between the constructs characterizing them. Model development was based on the premise that pollen quality perception affects consumer satisfaction. To test this premise, a reflexive measure model was used to design the Pollen Preferences Determination Questionary (PPDQ). Data from a pilot sample were used to evaluate the measure and structural models via structural equations models fitted through partial least squares (SEM-PLS).  The results showed the validity of the PPDQ since the indicators load its constructs appropriately, particularly for satisfaction and intrinsic quality.